Contribution of the -455G/A Polymorphism at the β-fibrinogen Gene to Erythrocyte Aggregation in Patients with Coronary Artery Disease - Weng, Xiaoduan; Cloutier, Guy; Genest, Jacques, Jr. (Thrombosis and Haemostasis, 1999)
Background. A high level of red blood cell (RBC) aggregation has been consistently found in patients with coronary artery disease (CAD) in case-control studies. Plasma fibrinogen has been shown to promote RBC aggregability. The purpose of this study was to investigate the influence of the genetic variability of the β-fibrinogen gene on RBC aggregation in patients with CAD. Methods and Results. The genotype of the β-fibrinogen gene locus was determined by polymerase chain reaction using the restriction enzyme HaeIII for a G to A substitution at position -455 upstream from the transcriptional start site in 135 French Canadians with premature CAD (age: 51 ± 7 years). Indices measuring the RBC aggregation kinetics (S10) and shear resistance of the aggregates (γS) were obtained by laser reflectometry. Patients were separated into groups by using the medians of S10 and γS. Using χ2 analyses, the distribution of the -455GG, -455GA, and -455AA genotypes in the groups with high levels of S10 (0.43, 0.49, and 0.08) and γS (0.45, 0.49, and 0.06) were found to be significantly distinct from those in the groups with low levels of S10 (0.67, 0.27, and 0.06; p <0.05) and γS (0.70, 0.23, and 0.07; p <0.01). High levels of RBC aggregation were closely associated with the rare -455A allele. Multivariate linear regression analyses showed that S10 was positively correlated with the linear combination of the fibrinogen concentration, age, and the -455G/A genotype (adjusted r = 0.63, p <0.0001). Fibrinogen and age were positive determinants, and HDL-cholesterol was a negative predictor of γS (adjusted r = 0.51, p <0.0001). Conclusion. These findings support the hypothesis that RBC hyperaggregation in premature CAD may be associated with the β-fibrinogen -455G/A polymorphism. This association may be explained by a change in the concentration and/or the functional properties of the fibrinogen protein.
Keywords: Erythrocyte aggregation; β-fibrinogen gene; genetics; coronary artery disease; fibrinogen; lipids; lipoproteins